True Diaphragmatic Hernia (Morgagni Hernia) Incidentally Diagnosed with Positive Contrast Peritoneography in a Cat: A Rare Case Report and a Review - Jack-Yves Deschamps; Théo Corbarieu; Nour Abboud; Françoise A. Roux (Veterinary Sciences, 2024)
An 18-month-old neutered male domestic shorthair cat was presented for an emergency consultation after falling from the second floor. The cat sustained minor traumatic injuries but did not exhibit dyspnea. Routine radiographic examination raised suspicion of a diaphragmatic hernia, but the circumscribed nature of the soft tissues visible in the thorax was atypical for a classic traumatic diaphragmatic hernia. A positive contrast peritoneography highlighted the likely presence of a hernial sac, which strongly suggested a “true diaphragmatic hernia”, also known as “pleuroperitoneal hernia”. This diagnosis was confirmed during laparotomy, which allowed for the visualization of a 3 cm radial diaphragmatic defect in the right ventral quadrant of the pars sternalis. The diaphragm’s edges were rounded. A portion of the falciform ligament and a part of the omentum were protruding through the defect and were contained within a hernial sac. Herniorrhaphy was performed. The cat recovered without complications. Given its presentation and location, ventrally and to the right, this anomaly is analogous to what is described in humans as “Morgagni hernia”. Six other cases of Morgagni hernias have probably been reported in cats but were not identified as such. This case underscores the utility of peritoneography, a straightforward technique useful for diagnosing diaphragmatic hernias, which enables differentiation between acquired traumatic forms and congenital forms, particularly peritoneopericardial hernias and pleuroperitoneal hernias. True diaphragmatic hernias are almost always serendipitous discoveries.